2019
DOI: 10.1016/j.jid.2018.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Psoriasis-Like Inflammation by PCSK9

Abstract: Psoriasis is a systemic inflammatory disease, associated with metabolic disorders, including high level of lowdensity lipoprotein. PCSK9, which promotes the degradation of low-density lipoprotein receptors and, therefore, the increased concentration of circulating low-density lipoprotein, is also involved in inflammation. This study aims to examine the role of PCSK9 in psoriasis and to investigate the potential of topically applying small interfering RNA targeting Pcsk9 as a psoriasis treatment. We investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 25 publications
4
39
0
Order By: Relevance
“…In the present study, we found that serum PCSK9 concentration was significantly elevated in psoriatic patients compared to the controls. Luan et al suggested a possible role for PCSK9 in the course of this disease and further, proved that suppression of PCSK9 inhibits hyperproliferation of keratinocytes through inducing apoptosis [27]. According to these and our own results, we assume that PCSK9 is a novel biomarker of psoriasis, but not of its severity.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In the present study, we found that serum PCSK9 concentration was significantly elevated in psoriatic patients compared to the controls. Luan et al suggested a possible role for PCSK9 in the course of this disease and further, proved that suppression of PCSK9 inhibits hyperproliferation of keratinocytes through inducing apoptosis [27]. According to these and our own results, we assume that PCSK9 is a novel biomarker of psoriasis, but not of its severity.…”
Section: Discussionsupporting
confidence: 75%
“…To our knowledge, there is only one paper investigating PCSK9 in psoriasis. Luan et al proved overexpression of PCSK9 in psoriatic lesions, indicating its important role in psoriasis, however the distinct relationship with lipid disorders should be further explored [27]. After considering these data, we maintained the thesis that PCSK9 seems to play a role in psoriasis and its association with the proatherogenic lipid profile, however further investigations are needed.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…PCSK9 inhibitor is already approved to treat hyperlipoproteinemia (113, 114). Our previous study reported that suppressing PCSK9 inhibited the hyper-proliferation of keratinocytes and reduced the psoriasis-like inflammation via the NFκB pathway (115). Interestingly, according to the structure analysis, PCSK9 C-terminal cysteine-rich domain (CRD) reveals structural homology with resistin (116).…”
Section: Mechanisms Of Mets and Skin Diseasesmentioning
confidence: 99%